2006
DOI: 10.1002/anie.200600433
|View full text |Cite
|
Sign up to set email alerts
|

Orthogonal Glycosylation Reactions on Solid Phase and Synthesis of a Library Consisting of a Complete Set of Fucosyl Galactose Isomers

Abstract: A dream team: Orthogonal glycosylation and solid‐phase synthesis were shown to be an excellent combination for polysaccharide synthesis (see scheme). The method was applied to generate a complete library of structural isomers with an L‐fucosyl‐D‐galactose sequence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(15 citation statements)
references
References 35 publications
0
14
1
Order By: Relevance
“…A 4‐aminobutyl glycoside ( 1 ) was found to generate a C‐ion species with a hemiacetal structure under CID conditions. Despite our previous finding on energy dependence in the dissociation of anomeric isomers, the dissociation of a pair of anomers of 4‐aminobutyl glycosides were indistinguishable 22–27. This suggested the dissociation mechanism is different from those of ordinary glycosides.…”
Section: Resultscontrasting
confidence: 62%
See 1 more Smart Citation
“…A 4‐aminobutyl glycoside ( 1 ) was found to generate a C‐ion species with a hemiacetal structure under CID conditions. Despite our previous finding on energy dependence in the dissociation of anomeric isomers, the dissociation of a pair of anomers of 4‐aminobutyl glycosides were indistinguishable 22–27. This suggested the dissociation mechanism is different from those of ordinary glycosides.…”
Section: Resultscontrasting
confidence: 62%
“…In such a case, an approach based on principal component analysis might be used, however, the source of information to be analyzed has been far from suitable and consists of limited structural isomers only 20, 21. For this reason, a combinatorial oligosaccharide library consisting of isomeric compounds with logical structural arrangements should provide indispensable information regarding structural characteristics 22–27. Energy‐resolved mass spectrometry (ERMS) has been used to address the energy dependence of structures of isomeric oligosaccharides where it was found that the lability of glycosides differs for anomeric configurations and linkage positions 28–34.…”
Section: Introductionmentioning
confidence: 99%
“…A study by Kanie et al. gives a broad comparative picture, as the group synthesized a wide range of fucosyl–galactosyl oligosaccharides in both the solution and solid phase …”
Section: Glycosylationsmentioning
confidence: 99%
“…The information accumulated, which is produced from a saccharide under analysis, is then compared with either the spectra or parameters obtained from CID experiments of product ions 27. Therefore, we are currently synthesizing an oligosaccharide library as the source of structural information 28–33…”
Section: Introductionmentioning
confidence: 99%